Physico-chemical characteristics of Figs Herbal Tea (Ficus racemosa L.) as a functional antidiabetic drink - Dewi, Yuli Kusuma; Suryani, Novia (Journal of Natural Sciences and Mathematics Research, 2024)
(Ficus racemosa L.) contain secondary metabolite compounds such as flavonoids, saponins, alkaloids, steroids, and tannins that have potential as a source of antioxidants. This study aims to determine the drying temperature variations on physicochemical characteristics of figs as an antidiabetic functional drink. The research methods begin by drying figs at various temperature (50°C, 60°C, and 70°C). The phytochemical test was followed by qualitative color change. The moisture content measurement was done using the thermogravimetric method. Then, the FTIR instrument identified the functional groups of organic compounds. Phytochemical analysis revealed the presence of flavonoids and tannins in all tea samples, regardless of drying temperature. FTIR spectroscopy confirmed the presence of phenolic compounds, characterized by O-H, Csp, and C=O enol groups. The pH of the tea at 50°C, 60°C, and 70°C, was 6.13; 5.64; and 5.59, the acidity of the pH obtained was indicated by the presence of phenolic compounds in all samples. The tea's moisture content was found to be within the Indonesian National Standard (<8%) at 60°C and 70°C, were 5.50% and 4.10%. Thus, fig tea, dried at 60°C or 70°C, can be developed as a functional antidiabetic drink.